Otimização do processo de produção de etanol de segunda geração em um sistema integrado à primeira geração - Carpio, Roymel Rodríguez (2019)
Two con gurations of the integrated sugarcane biore nery for producing rstand second-generation ethanol were modeled and simulated in EMSO. The rst con guration considers the xylose biodigestion for producing biogas. Meanwhile, the second con guration implements the xylose fermentation for obtaining ethanol. The developed simulations of the biore nery are useful tools for future studies and researches. In addition, a surrogate assisted optimization framework was developed in Matlab. The framework was based on the probability of improvement method, but with some modi cations that allowed dealing with constraints and improved the e ciency of the original algorithm. The developed framework was used for solving optimization problems involving the biore nery. None con guration of the biore nery was economically feasible. However, the xylose fermentation case presented better economic performance than the xylose biodigestion case. It is possible to increase the ethanol production up to 23% in both con gurations. Nevertheless, ethanol production increase greater than 21% lead to signi cant deterioration of economic indices. Most of the optimal con gurations were achieved for enzyme loading between 12-16 FPU/g, solids loading in the range of 14-17% and hydrolysis residence times above 68 hours.